2010
DOI: 10.1093/annonc/mdp358
|View full text |Cite
|
Sign up to set email alerts
|

Long-term endometrial effects in postmenopausal women with early breast cancer participating in the Intergroup Exemestane Study (IES)—a randomised controlled trial of exemestane versus continued tamoxifen after 2–3 years tamoxifen

Abstract: Background: The antiestrogen tamoxifen may have partial estrogen-like effects on the postmenopausal uterus. Aromatase inhibitors (AIs) are increasingly used after initial tamoxifen in the adjuvant treatment of postmenopausal early breast cancer due to their mechanism of action: a potential benefit being a reduction of uterine abnormalities caused by tamoxifen. Patients and methods: Sonographic uterine effects of the steroidal AI exemestane were studied in 219 women participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 29 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…In patients who switched to anastrozole following 2 years of tamoxifen (n = 1,618), there was only 1 case of endometrial cancer [78]. An endometrial IES substudy in 219 patients showed that abnormal endometrial thickening (C5 mm) was observed within 6 months in 36% of patients receiving exemestane; the incidence of endometrial cancer was not reported [17]. In the sequential groups of the BIG 1-98 trial, endometrial cancer developed in 4 patients (0.1%) [31].…”
Section: Gynecologic Adverse Events Associated With Aromatase Inhibitorsmentioning
confidence: 99%
“…In patients who switched to anastrozole following 2 years of tamoxifen (n = 1,618), there was only 1 case of endometrial cancer [78]. An endometrial IES substudy in 219 patients showed that abnormal endometrial thickening (C5 mm) was observed within 6 months in 36% of patients receiving exemestane; the incidence of endometrial cancer was not reported [17]. In the sequential groups of the BIG 1-98 trial, endometrial cancer developed in 4 patients (0.1%) [31].…”
Section: Gynecologic Adverse Events Associated With Aromatase Inhibitorsmentioning
confidence: 99%
“…Thus, if a subject is considering discontinuing tamoxifen due to adverse effects, they may be changed to treatment with the aromatase inhibitors, or vice versa. For instance, endometrial thickening associated with tamoxifen use, determined by transvaginal ultrasound, was reversed in subjects swapped to exemestane in the IES [36]. However, there is no evidence that such a change improves adherence to oral endocrine therapy.…”
Section: Interventions To Minimise Adverse Effectsmentioning
confidence: 99%
“…Numerous studies have investigated CYP2D6 polymorphism, demonstrating the role of tamoxifen metabolism in determining the risk of breast cancer recurrence. Specific side effects of tamoxifen have been associated with CYP2D6 mutations [1,2,3,4,5,6,7,8,9,10,11,12,13,14,17,18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…The use of tamoxifen may also result in changes to the lipid profile [8,9,10], bone mineral density (BMD) [11], and endometrial thickness (ET) [12,13]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation